Physics Concept Understanding Training Based on Multirepresentation and Inclusion for Students of SMP Negeri 81 Central Maluku - Jamaludin, Jamaludin; Batlolona, John Rafafy (Pascasarjana Universitas Mataram, 2024)
Science learning is a subject at the Junior High School level whose material is an integration of biology, chemistry and physics. However, there are still many teachers who do not have a science education background. This can be seen in the Eastern Indonesia region, where science teachers come from a certain discipline background, namely Biology, Physics and Chemistry. This is very disruptive in improving students' conceptualization. For example, biology teachers must teach physics concepts or vice versa. This situation makes it impossible to improve the quality of students, especially in physics learning. This is a concern and a separate note from the Government. Therefore, one of the activities carried out to improve students' conceptualization in physics is throughCommunity service activities (PKM). This activity is in the form of training with the aim of improving students' conceptualization in learning physics, especially Newton's law which is still a mistake and debate among students. This activity was carried out face-to-face for 84 students and accompanied by the principal and science teachers. The result of this activity is that students' conceptualization of Newton's Law increased, where students were able to answer several questions in the form of several physics cases from lecturers as activity speakers. In addition, there were many critical and unique questions given by students related to the phenomena they encountered in their environment related to Newton's Law.